MANAGEMENT METHOD OF ELECTRICITY GENERATION SYSTEM USING WIRELESS TECHNOLOGIES - Korniienko, Yehor; Liashenko, Oleksii; Torba, Aleksandr (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The subject of the study is the method of control and monitoring of the electricity generation system. The goal of the work is to investigate and develop a method for controlling the electricity generation system using wireless technologies. Relevance. The issues of energy efficiency and the use of alternative energy sources are relevant and important in modern conditions. In particular, solar energy is one of the most perspective areas in solving these problems. It is necessary to have the ability to monitor and control the generation process for optimal use of solar energy. The developed method should control the power generation system using wireless technologies and have flexible modes of operation. The development of the method of effective search for the point of maximum power and the power generation system in general is one of the most important tasks of the work. The object of the study is the process of control and monitoring of the electricity generation system. Research methods. Solar panel operation methods at maximum power: PWM (Pulse Width Modulation) and MPPT (Maximum Power Point Tracking). Results. The management method for the electricity generation system using wireless technologies is proposed in this work. A solar panel and a generator were chosen for electricity generation. The control of generation and system operation is based on the work of a microcontroller, which, in turn, transmits current data and the ability to control the system to a mobile application via a Wi-Fi module. This method can be used in a "Smart Home" system and other systems aimed at sustainable energy supply for consumers. Conclusion. The developed management method of the electricity generation system is planned to be used in systems of sustainable power supply for consumers. The method can be improved by integrating with other wireless technologies and adding other objects of electricity generation in the future.